Regulatory Ambiguity in Iddah: The Intersection of Circular Letters and Sirri Marriage Practices in Pontianak City - Q. Zaman; Vinna Lusiana; Ari Widyawati (JURNAL AT-TURAS, 2025)
This study investigates the critical issue of Regulatory Ambiguity surrounding the iddah period, specifically examining the friction between the Indonesian Circular Letter No. P-005/DJ.III/HK.00.7/10/2021 and the persistent, widespread practice of unregistered (sirri) marriage in Pontianak City. This intersection creates a crucial challenge to the coherence of Islamic Family Law, amplifying wider theoretical debates on Legal Dualism and the effectiveness of state intervention in personal status matters, ultimately jeopardizing women's rights and the legal protection of children. The primary purpose is to systematically identify the systemic causes of this discrepancy and analyze its profound impact on legal certainty and the state's authoritative capacity regarding matrimonial enforcement. Employing a combined juridical-normative and empirical approach, the research utilized legal document analysis alongside in-depth, strategic interviews with 10 key informants, comprising both officials from the Office of Religious Affairs (KUA) and citizens directly involved in sirri marriages, thus providing credible insights into the practical realities of legal pluralism. Findings reveal a profound administrative breakdown, exemplified by the critical statistic that 93% of KUA officials demonstrate a failure to distinguish accurately between iddah talak raj'i (revocable divorce) and iddah talak ba'in (irrevocable divorce). This lack of administrative competency directly translates into a systemic vulnerability, where legal loopholes are routinely exploited, leading to the disenfranchisement of wives and children in property and inheritance claims. This article contributes significantly to the discourse on Islamic Family Law Reform, providing an evidence-based framework for jurisprudential clarity that promotes judicial authority and ensures equitable enforcement of marital rights in the long term